1987
DOI: 10.1159/000184490
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Reduces Depression and Increases the Performance of Pleasant Activities in Hemodialysis Patients

Abstract: This study compares the effects of a structured exercise training program to the therapeutic benefits of a ‘support’ group on the depressed mood and reduced performance of pleasant activities by hemodialysis patients. After 6 months of an aerobic exercise training program, the 10 exercisers showed a significant increase in maximal aerobic capacity (VO2max) and a significant decrease in dysphoric mood when compared to 7 patients attending the support group. Support group participants reported a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 12 publications
1
49
0
1
Order By: Relevance
“…Despite the inconsistent association between aerobic physical activity levels and mortality in patients with CHF, we consistently observed higher HRQOL and lower depression symptom scores in patients with CHF who reported greater aerobic physical activity levels. Previous studies suggest that implementation of exercise programs in hemodialysis units improves HRQOL, reduces depression symptoms, and improves control of cardiovascular risk factors in patients on hemodialysis (12,(31)(32)(33)(34). Our findings provide additional support to the promotion of physical activity programs in hemodialysis units.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Despite the inconsistent association between aerobic physical activity levels and mortality in patients with CHF, we consistently observed higher HRQOL and lower depression symptom scores in patients with CHF who reported greater aerobic physical activity levels. Previous studies suggest that implementation of exercise programs in hemodialysis units improves HRQOL, reduces depression symptoms, and improves control of cardiovascular risk factors in patients on hemodialysis (12,(31)(32)(33)(34). Our findings provide additional support to the promotion of physical activity programs in hemodialysis units.…”
Section: Discussionsupporting
confidence: 69%
“…Because the analyses were cross-sectional, it is not possible to conclude on the direction of the associations of physical activity with depression symptoms and HRQOL. Results from randomized clinical trials, however, have shown that exercise training is associated with subsequent improvement in HRQOL and reduction in depression symptoms in patients on chronic dialysis (12,32).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, however, the present study is the first to examine determinants of ADL difficulty related to lower extremities after adjusting for confounders in HD patients. Walking speed and depressive symptoms, both predictors of ADL difficulty, have been reported to improve with adequate exercise training in HD patients [38,39]. Thus, exercise This study has some limitations worth noting.…”
Section: Discussionmentioning
confidence: 91%
“…The search resulted in 34 articles presenting the findings of 29 trials, including 9 uncontrolled trials (9/29, 31%) [5,6,7,8,9,10,11,12,13,14,15], 7 controlled trials (7/29, 24%) [16,17,18,19,20,21,22,23], and 13 RCTs (13/29, 45%) [24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. …”
Section: Results Of Searchmentioning
confidence: 99%